Scalp reconstruction using triple rotation flap and reverse posterior tibial flap for lower limb reconstruction in electric burn patient: a case report - Covarrubias, Eli Esaú Aguiñaga; Ayala, Ezequiel Ignacio Salcedo; Flores, Rubén Olivas; Flemate, Sergio Jacobo; Briones, Kasandra Rubí Domínguez; Vázquez, Rogelio Romero; Valdes, Francisco Barranco; Coronado Esquivel, Obed Asoid (International Journal of Research in Medical Sciences, 2024)
A 16-year-old male presented with a high-voltage electrical burn affecting the scalp, resulting in a 25 cm x 10 cm lesion, and third-degree burns on the right fifth toe and the base of the left first metatarsal. Initial management included a medial plantar flap for the pelvic limb injury, but perfusion failure led to the use of a reverse posterior tibial flap for coverage, along with a split-thickness skin graft. For the scalp injury, a triple rotation flap technique achieved adequate coverage. Four-day postoperative follow-up showed successful perfusion of the reverse tibial flap without complications, highlighting the challenges and need for adaptive surgical strategies in managing high-voltage electrical burns.